Antimicrobial mechanism of semi-bionic extracts of three traditional medicinal plants—Rheum palmatum L., Scutellaria baicalensis Georgi, and Houttuynia cordata Thunb—That can be used as antibiotic alternatives - Jiang, Hong; Bai, Zixia; Xu, Ziheng; Sun, Jian; Françoise, Hatungimana; Luan, Zuxiang; Wang, Hongjun (Frontiers in Veterinary Science, 2023)
The Chinese traditional medicinal plants Rheum palmatum L., Scutellaria baicalensis Georgi and Houttuynia cordata Thunb with the ratio was 108 : 65 : 27, to form a compound, named Dahuang Qinyu san (DQS). The active ingredients quercetin, emodin, baicalin and aloe-emodin were obtained by semi-biomimetic extract of DQS (SEDQS). However, the antibacterial mechanism of SEDQS against Salmonella is still unclear. The microwell-plate method was used to determine the Minimum Inhibitory Concentration (MIC) of SEDQS against Salmonella goose. In addition, the effect of SEDQS on the growth curve, respiratory metabolic system, cell wall, soluble protein and nucleic acid in bacterial liquid of Salmonella goose was detected by spectrophotometer and reagent kit. The effects of SEDQS on Salmonella goose DNA, binding gel blocking, virulence gene expression, and pathogenicity-related proteins were determined by gel electrophoresis, SDS-PAGE, and fluorescence quantitative PCR. The concentration of 1/4 MIC–2 MIC (2.27~18.2 mg/mL) SEDQS can significantly inhibit the normal growth of Salmonella goose, destroy the cell membrane structure of bacteria, and make nucleic acid, protein, and other contents leak (P<0.01). It also significantly inhibited the activities of succinate dehydrogenase (SDH) and malate dehydrogenase (MDH) (P<0.01) in a concentration-dependent manner. When the concentration of SEDQS was 1/2 MIC to 2 MIC (4.55~18.2 mg/mL), the expression levels of gyrB, fimA, filC, spvR, Hcp, and vgrG virulence genes (P<0.01) all decreased by more than 31%, 11%, 18%, 30%, 34% and 21% respectively compared with the control group. SEDQS could significantly inhibit the expression of six virulence genes, and play an important role in the pathogenicity of Salmonella goose infect host. The SEDQS could exert antibacterial pharmacological effects by inhibiting the growth and metabolism of Salmonella goose and inhibiting the expression of major virulence factors. It has potential application value as an antibiotic alternatives.